Pengaruh Kedisiplinan Guru terhadap Hasil Belajar Siswa Kelas VI pada Mata Pelajaran PAI - Saifudin; Muhammad Afifuddin; Khusnul Khotimah (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2022)
This study aims to determine teacher discipline, to determine student learning outcomes in PAI to prove the influence of teacher discipline on student achievement in PAI subjects.. This research is quantitative research and the research population is the sixth-grade students at SDI Ar-roudloh, totaling 26 people. Data collection was carried out using questionnaires and documentation of report cards for PAI subjects. Analysis of questionnaire data used percentage analysis and sted the effect using the